Pengaruh Minat dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran PKK TJKT - Fatimah, Fatimah; Darman, Regina Ade; Novita, Rini (TIN: Terapan Informatika Nusantara, 2024)
This study aims to determine the effect of learning interest and learning motivation on student learning outcomes in the Creative Products and Entrepreneurship (PKK) subject of the Computer Network and Telecommunication Engineering (TJKT) Department at SMK Negeri 1 Lembah Melintang. This study uses a quantitative approach with the ex post facto method, which examines events that have occurred. Data collection techniques include questionnaires, tests, and documentation. Data were analyzed using IBM SPSS Statistics 25 software. The results showed that there was a significant effect between learning interest (X1) on learning outcomes (Y) with a significance value of 0.008 (<0.05). In addition, learning motivation (X2) also has a significant effect on learning outcomes (Y) with a significance value of 0.001 (<0.05). The F test also shows that learning interest and learning motivation together have a significant effect on student learning outcomes. This is evidenced by the Fcount value of 7.713 which is greater than Ftable 3.195, with a significance of 0.001 (<0.05). From this study, it can be concluded that learning interest and learning motivation have a significant influence on student learning outcomes in the PKK subject in the TJKT Department of SMK Negeri 1 Lembah Melintang, both individually and collectively.